Criticality of the Rare Earth Elements: Current and Future Sources and Recycling - Simon M. Jowitt (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Rare earth elements (REE) are critical to our modern way of life, although potential primary and secondary sources of these elements and the economics of the REE sector remain somewhat poorly understood. This Special Issue focuses on furthering our understanding of the criticality and potential sources of rare earth elements as well as the economics of the REE sector. The papers in this Special Issue provide further insight into the full life cycle of REE, information that is vital to ensuring the existence of sustainable sources of these critical elements into the future.